Put the ball in Tunisia's court: New government and urgency of reform require modified EU approach - Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2020)
Despite a hostile environment, Tunisia's democratisation process since 2011 has survived and progressed. Yet crucial structural reforms to ensure effective governance, economic growth and resilient democracy have yet to be implemented. Elections in 2019 indicated a popular desire for a strong push for reforms. A new government took office at the end of February, but it remains to be seen how functional it will be. It encompasses parties whose views on certain questions are fundamentally opposed. This creates a dilemma for Tunisia's external partners: they would like to accelerate the pace of reforms but have little to show for their attempts to prod Tunisia into action. One option for spurring Tunisian initiative would be more targeted incentives for reforms and clearer conditionalities for financial assistance. Germany's reform partnerships are already a move in that direction, and Germany could use its EU Council Presidency in the second half of 2020 to persuade external donors to take a common line.
Keywords: 320